Effectiveness of exercise interventions on fall prevention in ambulatory community-dwelling older adults: a systematic review with narrative synthesis - Sadaqa, Munseef; Németh, Zsanett; Makai, Alexandra; Prémusz, Viktória; Hock, Márta (Frontiers in Public Health, 2023)
Objective To present a systematic review of randomized controlled trials which summarizes the effects of community-based resistance, balance, and multi-component exercise interventions on the parameters of functional ability (e.g., lower extremities muscle strength, balance performance and mobility). Methods This PROSPERO-registered systematic review (registration no. CRD42023434808) followed the PRISMA guidelines. Literature search was conducted in Cochrane, Embase, Ovid Medline, PEDro, Pubmed, Science Direct, Scopus and Web of Science. We included RCTs that investigated the following interventions: lower extremity strengthening, balance and multi-component exercise interventions on ambulatory community-dwelling adults aged ≥65 years. Results Lower extremity strengthening exercises revealed significant effects on the strength of lower extremity, balance outcomes and mobility. Balance exercises reduce the rate of injurious falls, improve static, dynamic and reactive balance, lower extremity strength as well as mobility. Multi-component exercise training reduces medically-attended injurious falls and fallers, incidence of falls, fall-related emergency department visits as well as improves mobility, balance, and lower extremity strength. Conclusion Physical exercises are effective in improving the components of balance, lower extremity strength, mobility, and reducing falls and fall-related injuries. Further research on fall prevention in low-income countries as well as for older adults in vulnerable context is needed.